Empirical Evidence Governance Innovation in Public Service (Jurnal Bina Praja, 2021)
Innovation in government activities is more directed in public services, although innovation can emphasize processes, development, planning, policies, and other activities. This research discusses governance innovation from empirical evidence that applied innovation cannot provide maximum results. The cause, government innovation that is not realized, appears only as a ceremonial act in government activities. Qualitative method analysis describes experiences, perceptions, responses through facts found in the informant's experience. This study was conducted in the Population and Civil Registration Record Office of Southeast Aceh Regency, starting from September to November 2020. In-depth interviews conducted with informants of this research consisted of government or executive, legislative, related institution, and citizen. Our field findings use the technique of hermeneutics to interpret various views that we can learn to look at the subject from every angle of knowledge (public administration, management, politics, innovation, and technology). That innovation should be supported by policies that result from decision-making, manager expertise, developed through long-term evaluation, and innovation as the basis for the quality of government public services. Governance innovation focuses on innovative action through various government instruments that lead to the simplification of action towards quality public services. For this reason, government, innovation, and how to manage are modes that continue to exist in administrative reform in government institutions with governance innovation that influence each other.
Keywords: civil registration; governance innovation; public service